2017
DOI: 10.1021/acs.jpcc.7b09959
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Relaxation Dynamics of Luminescent Copper Nanoclusters (Cu7L3) and Efficient Electron Transfer to Functionalized Reduced Graphene Oxide

Abstract: Luminescent copper nanoclusters (Cu NCs) have emerged as fascinating nanomaterials for potential applications in optoelectronics, catalysis, and sensing. Here, we demonstrate the synthesis of L-cysteinecapped Cu NCs in aqueous medium having a bright cyan emission (489 nm) with a quantum yield of 6.2%. The structure of the Cu NCs (Cu 7 L 3 ) is investigated by using density functional theory (DFT) calculation and mass spectrometric study. Further, time-dependent density functional theory (TD-DFT) calculations p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 70 publications
(106 reference statements)
3
61
0
Order By: Relevance
“…Mass spectrometric analysis showed that the Cu NCs@AA core was composed of 5–7 copper atoms, and the outside of the copper core was protected by 4 AA ligands. This structure was similar to the green fluorescent Cu NCs protected by L-cysteine prepared by the Amitava team [ 31 ], which proved the rationality of the Cu NCs@AA structure. At the same time, it reflected the size-dependent fluorescence properties of the metal nanoclusters.…”
Section: Resultssupporting
confidence: 71%
“…Mass spectrometric analysis showed that the Cu NCs@AA core was composed of 5–7 copper atoms, and the outside of the copper core was protected by 4 AA ligands. This structure was similar to the green fluorescent Cu NCs protected by L-cysteine prepared by the Amitava team [ 31 ], which proved the rationality of the Cu NCs@AA structure. At the same time, it reflected the size-dependent fluorescence properties of the metal nanoclusters.…”
Section: Resultssupporting
confidence: 71%
“…The fast decaying component (s 1 ) corresponds to electron transfer from the conduction band of the nanoparticle to rGO and the second term (s 2 ) is due to electron transition from an intermediate defect state to the valence band of the nanoparticle. 56,57 Interestingly, from Table 1 it is observed that the fast component for C1 is twice as much as that for C2 (0.50 ns vs. 0.26 ns) whereas the slow time scale is comparable for both. The decrease in the fast component signies a better transfer rate of photogenerated electrons to rGO in C2.…”
Section: Resultsmentioning
confidence: 89%
“…Fluorescent Cu NCs were synthesized following an earlier reported protocol with some modifications. 26 In brief, 0.2 mL of 100 mM Cu(NO 3 ) 2 ·3H 2 O solution was diluted with 19 mL of HPLC water in a round-bottom flask under vigorous stirring. The mixture turned faint green immediately on adding 4.8 mg of l -cysteine thereafter under nitrogen atmosphere.…”
Section: Experimental Sectionmentioning
confidence: 99%